Rac1 GTPase silencing counteracts microgravity‐induced effects on osteoblastic cells. Issue 9 (5th June 2014) - Guignandon, Alain; Faure, Céline; Neutelings, Thibaut; Rattner, Aline; Mineur, Pierre; Linossier, Marie‐Thérèse; Laroche, Norbert; Lambert, Charles; Deroanne, Christophe; Nusgens, Betty; Demets, René; Colige, Alain; et al.
Abstract : Bone cells exposed to real microgravity display alterations of their cytoskeleton and focal adhesions, two major mechanosensitive structures. These structures are controlled by small GTPases of the Ras homology (Rho) family. We investigated the effects of RhoA, Rac1, and Cdc42 modulation of osteoblastic cells under microgravity conditions. Human MG‐63 osteoblast‐like cells silenced for RhoGTPases were cultured in the automated Biobox bioreactor (European Space Agency) aboard the Foton M3 satellite and compared to replicate ground‐based controls. The cells were fixed after 69 h of microgravity exposure for postflight analysis of focal contacts, F‐actin polymerization, vascular endothelial growth factor (VEGF) expression, and matrix targeting. We found that RhoA silencing did not affect sensitivity to microgravity but that Rac1 and, to a lesser extent, Cdc42 abrogation was particularly efficient in counteracting the spaceflight‐related reduction of the number of focal contacts [‐50% in silenced, scrambled (SiScr) controls vs. ‐15% for SiRac1], the number of F‐actin fibers (‐60% in SiScr controls vs. —10% for SiRac1), and the depletion of matrix‐bound VEGF (‐40% in SiScr controls vs. ‐ 8% for SiRac1). Collectively, these data point out the role of the VEGF/Rho GTPase axis in mechanosensing and validate Rac1‐mediated signaling pathways as potential targets for counteracting microgravity effects.—Guignandon, A., Faure, C., Neutelings, T., Rattner, A., Mineur, P., Linossier, M.‐T., Laroche, N., Lambert, C., Deroanne, C., Nusgens, B., Demets, R., Colige, A., Vico, L. Rac1 GTPase silencing counteracts microgravity‐induced effects on osteoblastic cells. FASEB J. 28, 4077‐4087 (2014). www.fasebj.org